PH stimulus-disaggregated BODIPY: an activated photodynamic/photothermal sensitizer applicable to tumor ablation. Issue 13 (20th January 2020) - Liu, Yongchao; Xu, Chengyan; Teng, Lili; Liu, Hong-Wen; Ren, Tian-Bing; Xu, Shuai; Lou, Xiaofeng; Guo, Haowei; Yuan, Lin; Zhang, Xiao-Bing
Abstract : A pH activated photodynamic/photothermal sensitizer applicable to tumor ablation. Abstract : Herein, we report a pH stimulus-disaggregated BODIPY sensitizer (PTS) with low background-toxicity for achieving activated photodynamic/photothermal tumor therapy. Both the photodynamic and photothermal properties of PTS can be activated under acidic conditions, and PTS exhibits excellent antitumor properties, which is revealed by both in vitro and in vivo tests.